The Determinant Factors of Regional Development Toward Land Use Change in Deli Serdang. (March 2017) - Lindarto, D; Sirojuzilam,; Badaruddin,; Dwira,
Abstract: The concept of regional development Mebidangro (Medan, Binjai, Deli Serdang, and Karo) creating neighboring region hinterland Medan city with Deli Serdang Regency especially in Tembung village, Percut Sei Tuan District. Population structure in Tembung shows occurrence condition of rural-urban change which seen from the sprawl land use change. The aim of the study is to reveal the genius locus as one of land use change factors. The study conducted with quantitative approach intended at obtaining variables which describing several factors forming land use change. Descriptive approach intended to give an idea, justification, and fact-finding with correct interpretation. Data collected through a purposive sampling of 300 respondents who have built the house between 2010 till 2014. With overlay figure/ground technique, scoring analysis, descriptive quantitative and SEM (Structural Equational Models) gained a result that place character/genius locus (p=0, 007) potentially as one of the main land use change driving factors besides accessibility (p=0, 039), infrastructure (p=0, 005), social-economic p=0, 038). Topographic (p=0, 663) was inversely potentially. The implication of the findings is required intensive control in space utilization considering the rapid change in land use transformation that tend to have the negative impact of urban sprawl.